Electoral Reform in Japan: A Comparative Constitutional Law Perspective - Asaka, Kichimoto (Victoria University of Wellington Law Review, 1997)
The electoral systems of both Japan and New Zealand were recently reformed, and both states had their first elections under the new regimes in October 1996. This article considers some features of the two electoral systems from the point of view of the legal context in which the electoral reforms were made, and of the main reasons for those reforms.